Pleasantness Ratings for Harmonic Intervals With Acoustic and Electric Hearing in Unilaterally Deaf Cochlear Implant Patients - Spitzer, Emily R.; Landsberger, David M.; Friedmann, David R.; Galvin, John J. (Frontiers in Neuroscience, 2019)
Background: Harmony is an important part of tonal music that conveys context, form and emotion. Two notes sounded simultaneously form a harmonic interval. In normal-hearing (NH) listeners, some harmonic intervals (e.g., minor 2nd, tritone, major 7th) typically sound more dissonant than others (e.g., octave, major 3rd, 4th). Because of the limited spectro-temporal resolution afforded by cochlear implants (CIs), music perception is generally poor. However, CI users may still be sensitive to relative dissonance across intervals. In this study, dissonance ratings for harmonic intervals were measured in 11 unilaterally-deaf CI patients, in whom ratings from the CI could be compared to those from the normal ear. Methods: Stimuli consisted of pairs of equal amplitude MIDI piano tones. Intervals spanned a range of two octaves relative to two root notes (F3 or C4). Dissonance was assessed in terms of subjective pleasantness ratings for intervals presented to the NH ear alone, the CI ear alone, and both ears together (NH+CI). Ratings were collected for both root notes for within- and across-octave intervals (1-12 and 13-24 semitones). Participants rated the pleasantness of each interval by clicking on a line anchored with “least pleasant” and “most pleasant”. A follow-up experiment repeated the task with a smaller stimulus set. Results: With NH-only listening, within-octave intervals minor 2nd, major 2nd, and major 7th were rated least pleasant; major 3rd, 5th, and octave were rated most pleasant. Across-octave counterparts were similarly rated. With CI-only listening, ratings were consistently lower and showed a reduced range. Mean ratings were highly correlated between NH-only and CI-only listening (r=0.845, p< 0.001). Ratings were similar between NH-only and NH+CI listening, with no significant binaural enhancement/interference. The follow-up tests showed that ratings were reliable for the least and most pleasant intervals. Discussion: Although pleasantness ratings were less differentiated for the CI ear than the NH ear, there were similarities between the two listening modes. Given the lack of spectro-temporal detail needed for harmonicity-based distinctions, temporal envelope interactions (within and across channels) associated with a perception of roughness may contribute to dissonance perception for harmonic intervals with CI-only listening.